“Ensayos para la extracción y Caracterización de aceite de sacha inchi (plikenetia volubilis L.) en el departamento de San Martín - Vela Saavedra, Liley (1995)
This research seeks to generate a new alternative to obtain oil, restoring and valuing oil native plants that occur in our raw material used for the research work, I collect Shanao district, province of Lamas for the extraction of oil hydraulic pressing method is used. The extraction process was agreed following cleaning flow and selection preparation, husking, grinding, drying and pressing the found optimum parameters, for the best performance of extraction are: fine grinding with particle size of 2.19 mm, humedád 6% and 60° c/1 drying time. Raw material, determined biometric measurements and the proximal chemical analysis, found that Sacha inchic almond contains 51% oil and 27% being one of the fundamentals of this oil, its high unsaturated, features since it contains 52% of linolenic acid, which makes it...